Actual prospects of single cell protein (SCP) in agriculture and industry. - Chacón Villalobos, Alejandro (Agronomía Mesoamericana, 2004)
Since the beginning of the XXth century, single cell protein production has represented a biotechnological option, which viability has been much argued, for the handling and profitable disposal of large amounts of agricultural and industrial waste materials. Due to the nature of this process, lots of pollution sources can be transformed into useful materials with industrial, nutritional and economical value. This paper overviews the historical evolution of single cell protein, its importance and applications, advantages and disadvantages of its use in industrial processes, the main microorganisms known to be a source of SCP, the most representative substrates used for their growth, the biochemistry and key operations of the industrial process, general economical facts and future prospects. Nutritional aspects such as composition, nutritional value and limitations of SCP as a source of protein for human consumption are also reviewed.